The Idea of Meaning in Iddo Landau: Reflections on the Philosophy of Education - Bermejo Fernández-Nieto, Javier (Philosophical Inquiry in Education, 2026)
Iddo Landau's ideas on the meaning of life and their potential ramifications for modern education are examined in this article. This essay starts off by criticizing contemporary existential pessimism and arguing in favor of the notion that we can still find purpose in a flawed world. It explores the cultural, philosophical, and educational factors that have made this question especially relevant in recent years. Through dialogue with authors such as Metz, Seachris, Grondin, Gesché, Eagleton, Schinkel and others, a proposal is articulated that defends the pedagogical relevance of the debate on meaning, especially in contexts of axiological pluralism and crisis of references. The main argument here is that Landau's work not only revives the importance of meaning in philosophy but also offers essential insights for a teaching approach that, by focusing on meaning, can effectively tackle today's educational challenges. The work concludes with a reflection on the need for the educational sphere to reflect on the meaning of life from a critical, existential and pluralistic perspective.